Identification of gender doctrine: Muhammadiyah women’s movement and the dynamic role of agencies in its implementation at the local level - Rahmaniah, Aniek; Susanti, Emy; Hendrarti, Dwi Windyastuti Budi; Sari, Ulfi Andrian (Department of Sociology, Faculty of Social and Political Sciences, Universitas Airlangga, 2024)
Women’s membership in the Muhammadiyah organization is based on the Islamic view of men and women as ethical agents in inviting goodness and avoiding evil. This theology indicates the importance of women’s role in the public sphere. This study aims to analyze and explore Muhammadiyah’s gender doctrine and agency dynamics in its implementation at the local level by Muhammadiyah women. The ethnomethodology approach was used in this study. Research data was obtained through observation activities, in-depth interviews, and direct involvement in the activities of the Muhammadiyah women’s movement for gender justice. This study was conducted in Malang City, taking into account the dynamics of gender implementation in the Muhammadiyah women’s movement in its efforts to realize gender justice. This research found that there has been gender segregation since 1939 which is reflected in the Muhammadiyah gender statute. In addition, it is written in Muhammadiyah’s gender demands book that there has been a domestication of gender issues, although later developments show that publications represent the spirit of gender equality. This study concludes that the Muhammadiyah women’s movement is not only about adjusting women’s roles in all activities as long as they are within Islamic parameters. In fact, the Muhammadiyah women’s movement has made many contributions to the public interest, from building educational facilities, health, to humanitarian activities.